Application of user interface Fuzzy Logic Toolbox for quality control of products and services - Hrihorenko, Igor; Drozdova, Tatyana; Hrihorenko, Svetlana; Tverytnykova, Elena (Національний технічний університет "Харківський політехнічний інститут", 2019)
In this work, the solution for the quality control of products and services is illustrated for the first time on examples of wine production and the provision of educational services in the university by creating a heuristic analyzer based on the Fuzzy Logic Toolbox interface of the Matlab program. There were also considered the problems of constructing quality control models with fuzzy logic for solving problems arising in cases when it is not possible to use classical statistical methods. The factors influencing the quality of products, in particular wine, and services on the example of providing education are analyzed, the possibility of using the fuzzy logic apparatus for determining the weight contribution of factors that ensure maximum quality is proved. Computer simulation using the Mamdani algorithm is performed, which consists of fuzzification with the definition of ranges of change of input values for each example, assigning the distribution functions for each input parameter; calculation of the rules, based on the adequacy of the model; defuzzification with the transition from linguistic terms to quantitative evaluation; graphical construction of the response surface using a centroid method with determination of the center of gravity of the response surface. The modeling has confirmed that the creation of a heuristic analyzer for determining the quality of wine and the quality of education is appropriate and necessary for preventing the production of substandard products and theprovision of substandard services.

В роботі вперше проілюстровано рішення задачі контролю якості продукції та послуг на прикладах виробництва вина і надання освітніх послуг у ВНЗ за допомогою створення евристичного аналізатора на базі інтерфейсу системи нечіткої логіки Fuzzy Logic Toolbox програми Matlab. Розглянуто питання побудови моделей контролю якості з нечіткою логікою для вирішення завдань, що виникають у випадках, коли немає можливості використовувати класичні статистичні методи. Проаналізовано фактори, що впливають на якість продукції, зокрема вина, і послуг на прикладі надання освіти, доведена можливість застосування апарату fuzzy logic для визначення вагового внеску факторів, які забезпечують максимальну якість. Проведено комп'ютерне моделювання за алгоритмом Mamdani, який складається з фазифікації з визначенням діапазонів зміни вхідних величин для кожного прикладу, завданням функцій розподілу для кожного вхідного параметра; обчислення правил,виходячи з адекватності моделі; дефаззифікації з переходом від лінгвістичних термів до кількісної оцінки; графічного побудови поверхні відгуку, використовуючи центроїдного метод з визначенням центру ваги поверхні відгуку. Моделювання підтвердило, що створення евристичного аналізатора для визначення якості вина і якості освіти доцільно і необхідно для того, щоб не допустити виробництво неякісної продукції і надання неякісних послуг.
Застосування призначеного для користувача інтерфейсу Fuzzy Logic Toolbox для контролю якості продукції та послуг
Keywords: heuristic analyzer; fuzzification; defuzzification; евристичний аналізатор; фазифікація; дефазифікація